A rapid and innovative extraction and enrichment method for the metaproteomic characterization of dissolved organic matter in groundwater samples. Issue 8 (10th December 2020) - Capriotti, Anna Laura; Aita, Sara Elsa; Cavaliere, Chiara; Cerrato, Andrea; Montone, Carmela Maria; Piovesana, Susy; Laganà, Aldo
Abstract: Metaproteomic analysis of aquifer systems provides valuable information on the microbial populations, their influence on drinking water quality, and the effect on human health. In the present paper, an extraction and enrichment method by C18 extra‐wide pore cartridge was developed, optimized, and applied for the first time to the metaproteomic characterization of dissolved organic matter in groundwater samples. In particular, three elution procedures were tested and compared on water spiked with a yeast protein extract to maximize the recovery of proteins from a complex matrix. The maximum protein recovery was obtained by the use of two sequential elution buffers, one employing a denaturing agent and the other one containing an acidified organic solvent. A comprehensive metaproteomic analysis of the dissolved organic matter of groundwater was then performed by nano‐high performance liquid chromatography coupled to high‐resolution mass spectrometry. A total of 239 proteins was identified; in agreement with the current knowledge on proteins in aquifer systems, most identified sequences derived from bacteria, protobacteria, and ciliates. The paper is the first metaproteomic study applied to groundwater samples with particular emphasis on the need for sample pretreatment to obtain comprehensive information on the proteome in dissolved organic matter.